Antifungal potential of marine bacterial compounds in inhibiting Candida albicans Yck2 to overcome echinocandin resistance: a molecular dynamics study - Alshahrani, Mohammed Merae (Frontiers in Pharmacology, 2024)
Candida albicans (C. albicans), a common fungal pathogen, poses a significant threat to immunocompromised individuals, particularly due to the emergence of resistance against echinocandins, a primary class of antifungal agents. Yck2 protein, a key regulator of cell wall integrity and signaling pathways in C. albicans, was targeted to overcome this resistance. A virtual screening was used to identify Yck2 inhibitors from marine bacterial compounds. Further re-docking, molecular dynamics simulations, and various analyses such as RMSD, RMSF, hydrogen bonding, free binding energy calculations, and RG-RMSD-based free energy landscape were conducted to evaluate the efficacy and stability of the identified compounds. Among the compounds screened, CMNPD27166 and CMNPD27283 emerged as the most promising candidates, demonstrating superior binding affinities, enhanced stability, and favorable interaction dynamics with Yck2, surpassing both the control and other compounds in efficacy. In contrast, CMNPD19660 and CMNPD24402, while effective, showed lesser potential. These findings highlight the utility of computational drug discovery techniques in identifying and optimizing potential therapeutic agents and suggest that marine-derived molecules could significantly impact the development of novel antifungal therapies. Further experimental validation of the leading candidates, CMNPD27166 and CMNPD27283, is recommended to confirm their potential as effective antifungal agents against echinocandin-resistant C. albicans infections.-IT Solubility (mol/l) 7.01E-08 1.93E-08 1.08E-13 9.62E-11 Silicos-IT class Poorly soluble Poorly soluble Insoluble Insoluble GI absorption High High Low High BBB permeant No No No No Pgp substrate Yes Yes Yes Yes CYP1A2 inhibitor No No No Yes CYP2C19 inhibitor No No No No CYP2C9 inhibitor No Yes No No CYP2D6 inhibitor Yes No No No CYP3A4 inhibitor